Energy savings and emission reductions in industrial boilers - Saidur, Rahman (Thermal Science, 2011)
Energy use of boiler fan motors has been estimated using energy audit data. Energy savings using variable speed drive by modulating fan speed has been estimated as well. Bill savings and associated emission reductions using variable speed drive have been estimated and presented. It has been found that 139,412, 268,866, 159,328, and 99,580 MWh electrical energy can be saved for 40, 60, 80, and 100 motor loadings, respectively for 60 speed reduction. Corresponding bill savings for the aforementioned energy savings have been found to be 7,318.335, 14,113.933, 8,363.812, and US 135,911.944 for 40, 60, 80, and 100 motor loadings, respectively, for 60 speed reduction. Along with energy savings, 69,770.744, 134,558.329, 79,738.065, and 49,836.603 kg of CO(2) emission can be avoided for the associated energy savings as a result of energy savings using variable speed drive for 40, 60, 80, and 100 motor loadings. Moreover, 32,503.558 GJ of fossil fuel can be saved for the flue gas temperature reduction as a result of reducing fan motor speed reduction. Flue gas energy savings for oxygen trim system has been estimated and found to be 549,310,130 GJ for 16.9 of excess air reduction with payback period less than a day.